Analysis Of Container Handling Damage At Makassar Container Terminal - Yeti Komalasari (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2022)
The purpose of this study was to determine the factors that cause container damage at the Soekarno-Hatta Makassar Container Terminal. This research was conducted at the Container Terminal of Soekarno-Hatta Port, Makassar. This study uses a qualitative descriptive method that uses information about the occurrence of further damage at the container terminal at Soekarno Hatta port, observations, interviews, with employees and the author looking for literature in the library related to the title of this study. The results showed that the factors causing damage to containers at the Soekarno-Hatta Port Container Terminal, Makassar Port were the operation of cranes that were not careful in handling containers so that the containers were damaged and the lack of maintenance which resulted in containers corroding.